Information and Communication Technologies in teaching methodologies: how you see yourself indicates how innovative you are - Maurandi-López, Antonio (2025)
Background. The pandemic showed that the use of new teaching methodologies supported by Information and Communication Technologies (ICT) can improve students’ teaching-learning processes and the acquisition of competences. Aims. The aim of this study was to analyze the external and internal factors, such as teachers’ self-concept, that influence the adoption of ICT in the application of active methodologies in their classes. Methods. Using a non-experimental, descriptive, and correlational quantitative design, a Likert-scale survey was administered to 556 high school teachers from different schools in Ecuador. The information collected was used to fit a generalized linear model that responded to the research objective. Results. The results showed a strong positive relationship and effect between teachers’ self-perception of their innovative capacity and their use of new technologies. On the other hand, their age and years of experience were found to have a negative effect on these variables, and significant differences were found in the use of digital resources between teachers in public and private schools, with more use of these tools in private schools. Conclusions. The use of ICT in the classroom in conjunction with innovative methodologies is influenced by many factors, not least of which is the self-perception of the teaching staff themselves.